Plasminogen Activator Inhibitor (PAI-1) and Non-insulin-dependent Diabetes in Pima Indians, South Asians and Europeans - Nagi, D K; Knowler, W C; Hanson, R L; Mohamed Ali, V; Yudkin, J S (Thrombosis and Haemostasis, 1996)
Activity of plasminogen activator inhibitor-1 (PAI-1), a potent inhibitor of fibrinolysis, is raised in non-insulin-dependent diabetes mellitus (NIDDM) and may contribute to excess macrovascular disease. We investigated the association of PAI-1 activity with NIDDM in Pima Indians, a racial group with low risk of coronary artery disease, but in whom the impact of NIDDM on the occurrence of coronary artery disease is similar to other racial groups. We studied 308 (136 nondiabetic, 172 diabetic) Pima Indians from Arizona, and 138 (98 nondiabetic, 40 diabetic) South Asians and 129 (80 non-diabetic, 49 diabetic) Europeans living in North London. PAI-1 activity was measured by a spectrophotometric assay, and insulin, intact proinsulin and des 31,32 proinsulin concentrations were measured employing highly specific monoclonal antibody-based assays. Compared with non-diabetic subjects, PAI-1 activity was significantly higher in subjects with NIDDM among South Asians (22.8 ± 7.3 vs. 17.4 ± 6.9 AU/ml, p <0.001) and Europeans (23.1 ± 6.6 vs. 16.5 ± 6.1 AU/ml, p <0.001) but not among Pima Indians (19.5 ± 9.6 vs. 18.5 ± 8.6 AU/ml, ns). The association of PAI-1 activity with diabetes remained statistically significant when controlled for age, sex, body mass index and waist-hip ratio, serum triglyceride and fasting insulin concentrations in South Asians (p <0.001) and Europeans (p <0.001). The relationships of PAI-1 activity with clinical and biochemical variables were similar in the three racial groups other than for fasting and 2 h plasma glucose concentrations which were significantly associated with PAI-1 activity in South Asians (partial r = 0.32 and 0.31) and Europeans (partial r = 0.44 and 0.50) but not in Pima Indians (partial r = 0.11 and 0.15). In Pima Indians with NIDDM, PAI-1 activity was similar in those treated with sulphonylureas, insulin, or no drugs for diabetes. In conclusion, the association of PAI-1 with diabetes differs in racial groups who are at different risk of NIDDM and ischaemic heart disease. Previously reported differences in the prevalence of ischaemic heart disease between diabetic and non-diabetic Pima Indians, and between non-diabetic subjects from the three racial groups, are unlikely to be due to differences in PAI-1 activity.